2008
DOI: 10.1037/0894-4105.22.3.412
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and motivational changes after bilateral lesions of the globus pallidus.

Abstract: This study investigated motivational changes in a 44 year-old man (PJ) who developed considerable reduction in spontaneous activity and speech, flat affect, social withdrawal, loss of interest, inability to "feel," and lack of concern regarding his medical condition after bilateral, focal, anoxic lesions of the globus pallidus. PJ and 30 male controls performed a task designed to parse hedonic evaluation, or liking, from incentive motivation, or wanting. Affective stimuli were presented on a computer screen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…We suggest that these VP neuronal signals for reward components could be related to reports of activity in human posterior VP positively correlated with pleasant food images (17) and mechanisms by which opioid and related stimulation in a VP hotspot can modulate the hedonic impact of sensory rewards (33,36,77). Conversely, one could speculate that impairment of hedonic signals in NAc-VP pathways could contribute to clinical manifestations of anhedonia or incentive motivation impairment in depression and related disorders (78) or to dysphoria after lesions encroaching on the VP hotspot (79)(80)(81).…”
Section: Reward Component Separation By Population Segregation and Fimentioning
confidence: 99%
“…We suggest that these VP neuronal signals for reward components could be related to reports of activity in human posterior VP positively correlated with pleasant food images (17) and mechanisms by which opioid and related stimulation in a VP hotspot can modulate the hedonic impact of sensory rewards (33,36,77). Conversely, one could speculate that impairment of hedonic signals in NAc-VP pathways could contribute to clinical manifestations of anhedonia or incentive motivation impairment in depression and related disorders (78) or to dysphoria after lesions encroaching on the VP hotspot (79)(80)(81).…”
Section: Reward Component Separation By Population Segregation and Fimentioning
confidence: 99%
“…Striatal and cingulate lesions would potentially be associated with less riskaverse (and more risk neutral) choices. A striatal lesion could reduce the ability to evaluate magnitude, an effect that is also implied by negative motivational changes in patients with globus pallidus lesions (Vijayaraghavan et al, 2008). Nevertheless, such a lesion could be compensated by functions in other areas, namely ventromedial prefrontal cortex.…”
Section: Combined Bold Signals Contributing To Decision Makingmentioning
confidence: 99%
“…Neurobiological studies have shown that lesions in reward and motivation circuits result in anhedonia [83,[98][99][100] with neuroimaging studies demonstrating decreased activation in the medial frontal cortex as a possible causative factor underlying abnormal positive affect processing in patients [101][102][103].…”
Section: Anhedoniamentioning
confidence: 99%